Dietary restriction causing iodine-deficient goitre. Issue 8 (11th June 2015) - Cheetham, Tim; Plumb, Emma; Callaghan, James; Jackson, Michael; Michaelis, Louise
Abstract : Iodine-deficient goitre was common in some parts of the UK prior to the introduction of salt iodisation. Many contemporary salt preparations do not contain much iodine, and there are renewed concerns about the iodine status of the population. We present a boy with severe allergy who developed goitre and significant thyroid dysfunction in association with an iodine-deficient 'food-restricted' diet. The case highlights the importance of a comprehensive nutritional assessment in all children on multiple food restrictions.